Considerations on the Critical Theory of Rahel Jaeggi - Florito Mutton, Alan Matías (Res Publica. Revista de Historia de las Ideas Políticas, 2022)
The aim of this paper is to examine Rahel Jaeggi's critical diagnosis of society. The paper begins by developing her analysis of the critique of ideology. Then we will show the central elements of her critical theory deployed in Alienation and Critique of Forms Life. The conclusion is that Jaeggi's critical theory is an immanent critique and a critique of the ideology of contemporary society.
Keywords: Critical Theory; Jaeggi; Alienation; Social Critiqu; Forms of Life